Assessment of Tribal Bison Worker Hazards Using Trusted Research Facilitators. Issue 4 (2nd October 2017) - Duysen, Ellen; Irvine, Kelsey; Yoder, Aaron; Topliff, Christina; Kelling, Clayton; Rajaram, Shireen
ABSTRACT: Objectives: Agriculture is one of the most hazardous industries in the United States. Within agriculture, livestock handling is particularly dangerous. While injury and fatality rates for bison handlers have not been reported, workers in many of the newly established tribal bison herds have limited safety training and animal handling experience, making this a vulnerable workforce. Veterinarians and herd managers, working with tribal bison herds, recognized the need for improvement in the working environment and for worker safety training. In response, partnerships were established and a pilot project was developed in order to characterize risks and hazards associated with bison handling under contemporary reservation field conditions. Individuals and organizations working as change agents included veterinarians at the University of Nebraska – Lincoln School of Veterinary Medicine, a tribal advocacy organization, the Intertribal Buffalo Council and researchers at the Central States Center for Agricultural Safety and Health at the University of Nebraska Medical Center. Methods: This is a mixed-methods study and data were gathered through closed and open-ended questions pertaining to bison worker safety hazards. A veterinarian gathered data through observational safety audits at bison herding locations. American Indian bison herd managers completed surveys using a convenience sampling method. Results: Findings indicate that the most common worker safety risks are associated with the use of high-stress handling methods and substandard facilities and equipment. Adverse environmental conditions also contribute to worker health risks. Most common causes of injuries included those caused by equipment and tools, adverse weather, and direct contact with animals. Conclusion: This collaborative research study contributes to a better understanding of hazards faced by tribal bison workers. Findings from this research influenced the ITBC in their decision to add worker safety and health training to the agenda of their yearly conference and promote tailgate trainings for their workers. UNL veterinarians have taken the lessons learned from this research and provided safety and health information to mangers of other non-tribal bison herds. This research partnership will continue with a 5-year research study focusing on best management practices and establishing training to improve the health and safety bison workers.